Refinancing of Credit Granted to a Consumer by Various Entities with Capital or Personal Links as a Practice Infringing Collective Consumer Interests - Paleczna, Magdalena (Journal of Finance and Financial Law, 2020)
There are various irregularities in creditors' actions, one of which is the refinancing of consumer credit granted to the consumer by various entities with capital or personal links. This is a phenomenon which has become apparent in the activities of lenders over the last few years and has been the subject of analyses by both the Financial Ombudsman and the President of the Office for Competition and Consumer Protection. The purpose of this article is to present the phenomenon of refinancing a credit granted to a consumer by various entities affiliated by capital or personally as an attempt to circumvent the application of Article 36a and Article 36c of the Act of 12 May 2011 on consumer credit and thus a practice infringing the collective interests of consumers pursu-ant to Article 24(1) and (2) of the Act of 16 February 2007 on Competition and Consumer Protection. The aim of the study is to present the phenomenon of refinancing a credit granted to a consumer by various entities with capital or personal links and to consider this phenomenon as a prohibited practice infringing the collective interests of consumers.